Legal Protection for Female Sexual Harassment Victims in Campus: Based on Indonesian Criminal Justice System Reviewed by Permendikbud Number 30 of 2021 - Joni Irawan; Indra Rukmono; Abustan Abustan; Brilian Ahmad Sugiono (CLEAR: Criminal Law Review, 2024)
This current study aims at perceiving the form of legal protection in accordance with the latest policy regarding the Prevention and Handling of Sexual Violence (PPKS) on campus, reviewed from the policy of the Minister of Education and Culture Regulation No. 30 of 2021. Sexual harassment is a crime committed by harassing, humiliating, insulting which results in psychological or physical disorders. This sexual crime does not only occur in the private, family, online game, office and company environment, but also happen in a college environment. Thereby, the current study set their focus to grasp the legal protection of female sexual harassment victims in a university environment and the legal protection for sexual protection in a university environment reviewed from the Minister of Education and Culture Regulation No. 30 of 2021. A normative legal study was piloted in the study. With the presence of the Minister of Education and Culture Regulation Edition 30 of 2021, all universities in Indonesia must prevent and overcome sexual violence. In addition, sexual harassment encompasses psychological violence, physical violence, economic violence, verbal violence and cyber-sexual violence. Kajian saat ini bertujuan untuk mempersepsikan bentuk perlindungan hukum sesuai dengan  kebijakan terbaru terkait Pencegahan dan Penanganan Kekerasan Seksual (PPKS) di kampus, ditinjau dari kebijakan Peraturan Menteri Pendidikan dan Kebudayaan No. 30 Tahun 2021. Pelecehan seksual adalah kejahatan yang dilakukan dengan melecehkan, mempermalukan, menghina yang mengakibatkan gangguan psikologis atau fisik. Kejahatan seksual ini tidak hanya terjadi di lingkungan pribadi, keluarga, game online, kantor dan perusahaan, tetapi juga terjadi di lingkungan perguruan tinggi. Dengan demikian, kajian saat ini menjadi fokus mereka untukmemahami perlindungan hukum terhadap korban pelecehan seksual perempuan di lingkungan universitas dan perlindungan hukum terhadap perlindungan seksual di lingkungan universitas yang ditinjau dari Peraturan Menteri Pendidikan dan Kebudayaan No. 30 Tahun 2021. Sebuah studihukum normatif diujicobakan dalam penelitian tersebut. Dengan hadirnya Peraturan Menteri Pendidikan dan Kebudayaan Edisi 30 tahun 2021, seluruh perguruan tinggi di Indonesia harus mencegah dan mengatasi kekerasan seksual. Selain itu, pelecehan seksual meliputi kekerasan psikologis, kekerasan fisik, kekerasan ekonomi, kekerasan verbal, dan kekerasan cyber-seksual.